Guinness Book of World Records, 1991 (New York Bantam Books, 1991)
As the world has grown and changed, as humankind has challenged its inner and outer limits, Guinness Book of World Records has been there to record every incredible fact and feat.
osc 9/11/2021
Ref
Keywords: McFarlan, Donald; McWhirter, Norris D; McCarthy, Michelle Dunkley; Young, Mark; Curiosities and Wonders